DNA Dyes-Highly Sensitive Reporters of Cell Quantification: Comparison with Other Cell Quantification Methods - Ligasová, Anna; Koberna, Karel (Molecules (Basel, Switzerland), 2021)
Cell quantification is widely used both in basic and applied research. A typical example of its use is drug discovery research. Presently, plenty of methods for cell quantification are available. In this review, the basic techniques used for cell quantification, with a special emphasis on techniques based on fluorescent DNA dyes, are described. The main aim of this review is to guide readers through the possibilities of cell quantification with various methods and to show the strengths and weaknesses of these methods, especially with respect to their sensitivity, accuracy, and length. As these methods are frequently accompanied by an analysis of cell proliferation and cell viability, some of these approaches are also described.
Keywords: fluorescenční barviva; Biological Assay; proliferace buněk; biotest; enzymatic conversion of substrate; Cell Count; Cell Proliferation; DNA dyes; cell metabolism; cell quantification; DNA; počet buněk; Fluorescent Dyes; viabilita buněk; Cell Survival